Carbapenemase-producing Enterobacteriaceae in Australian hospitals: outcome of point-prevalence screening in high-risk wards. Issue 2 (February 2019) - Brett, J.A.; Johnson, S.A.; Cameron, D.R.M.; Lane, C.R.; Easton, M.; van Diemen, A.; Sutton, B.; Bull, A.L.; Richards, M.J.; Worth, L.J.
Summary: Carbapenemase-producing Enterobacteriaceae (CPE) infections are increasingly reported in Australian hospitals, but prevalence is unknown. In 2016, Victorian hospitals conducted CPE point-prevalence surveys in high-risk wards (intensive care, haematology, transplant). Forty-three hospitals performed 134 surveys, with 1839/2342 (79%) high-risk patients screened. Twenty-four surveys were also performed in other wards. Inability to obtain patient consent was the leading reason for non-participation. In high-risk wards, no CPE cases were detected; three cases were identified in other wards. Since there is low prevalence in high-risk wards, continuous screening is not recommended. Targeted screening may be enhanced by review of patient consent processes.